Case report: Novel insights into hemorrhagic destruction of the brain, subependymal calcification, and cataracts disease - Abdallah Moady, Tameemi; Odeh, Marwan; Fedida, Ayalla; Segal, Zvi; Gruber, Maayan; Goldfeld, Moshe; Kalfon, Limor; Falik-Zaccai, Tzipora C. (Frontiers in Pediatrics, 2023)
Pathogenic variants in Junctional Adhesion Molecule 3 (JAM3/JAM-C; omim#606871) cause the rare recessive disorder: Hemorrhagic Destruction of the Brain, Subependymal Calcification and Cataracts (HDBSCC, OMIM#613730). Similar phenotype is universal, including congenital cataracts and brain hemorrhages with high mortality rate in the first few weeks of life and poor neurologic outcome in survivors. (1-4) We aim to describe and enlighten novel phenotypes and genotype of a new patient and review the literature regarding all reported patients worldwide.We report the prenatal and postnatal phenotype of a new patient with a novel pathogenic lossof-function variant in JAM3, who presented prenatally with cataracts and brain anomalies, and postnatally with brain hemorrhages, failure to thrive (FTT), progressive microcephaly, recurrent posterior capsule opacities and auditory neuropathy.This report enlightens novel possible functions of JAM3 in the normal development of the brain, ocular lenses, the auditory system and perhaps the gastrointestinal tract. This is the first report of cataracts evident as early as 23 weeks' gestation and a rare phenomenon of recurrent posterior capsule opacities despite recurrent posterior capsulectomy and anterior vitrectomy .We suggest that auditory neuropathy, reported here for the first time, is part of the phenotype of HDBSCC, probably due to endothelial microvasculature disruption of the peripheral 8 th nerve or perhaps due to impaired nerve conduction from the synapse to the brainstem.Prenatal cataracts, brain anomalies, FTT and auditory neuropathy are part of the phenotype of HDBSCC disease. We suggest including JAM3 in the gene list known to cause congenital cataracts, brain h emorrhages and hearing loss. Further studies should address the auditory neuropathy and FTT phenomena in knockout mice models. We suggest performing comprehensive ophthalmic, audiologic and gastroenterologic evaluations for living patients worldwide to further confirm these novel phenomena in this rare entity.